Knowledge, attitude, and practice of dentists in the management of medical emergencies in India: A cross-sectional study - Anabelle L.V.C. Fernandes; Jayraj B. Malik; Sulem R. Ansari; Sridhar Murali; Jayapriya Thirupathii (Elsevier, 2023)
Background: A medical emergency is an acute, unanticipated medical reaction or complication that threatens the patient's life or health and necessitates rapid attention or intervention. Since these emergencies can be life-threatening, the dentist's readiness is critical to avoid morbidity, mortality, and legal complications. Therefore, this study aims to assess dental students' and practitioners' knowledge, attitude, and practice in managing medical emergencies in India. Material and methods: A cross-sectional study was conducted at a private dental institute among 420 participants (318 males and 102 females) using a customized questionnaire consisting of sixteen questions - one open-ended and fifteen closed-ended. The data obtained was analysed using Chi-square test, Kruskal-Wallis H test, Mann -Whitney U test, and Spearman's rank correlation coefficient test. Results: Out of the 420 respondents, 416 (99.05 %) respondents believed that it is essential to obtain patients' vital signs (blood pressure, pulse, respiratory rate, temperature) before starting any treatment. However, 345 (82.14 %) respondents had not taken any course in managing medical emergencies and only 196 (46.67 %) respondents were confident in handling a medical emergency. There was a statistically significant association (P < 0.05) between the various qualifications and responses for the majority of the questions. Conclusion: There is a general lack of knowledge among all the respondents and a lack of positive attitude among undergraduates in dealing with medical emergencies.